Effect of lipid on formation of Maillard and lipid‐Maillard meaty flavour compounds in heated cysteine‐xylose‐methyl linoleate system. (16th June 2022) - Wang, Yutong; Xie, Jianchun; Zhang, Chenping; Xu, Yuxia; Yang, Xuelian
Abstract: The effect of lipid level and reaction temperature and time on the heated cysteine‐xylose reaction to form meaty flavours was investigated. The presence of 1% or 2% methyl linoleate inhibited the formation of volatile sulfur‐containing compounds and heterocyclic compounds via the Maillard reaction, that is Maillard compounds. However, the former was better because of the moderate inhibition and more compounds generated from the lipid‐Maillard interaction, that is lipid‐Maillard compounds. Partial least squares‐discriminant analysis suggested the lipid‐Maillard compounds were the main markers during varying dosage of methyl linoleate, reaction temperature (100–140°C) and reaction time (30–180 min). Lower temperatures increased formation of the Maillard compounds (eg, 2‐furfurylthiol) or lipid‐Maillard compounds (eg, 2‐pentylpyridine) with reaction time. However, high temperatures caused their amounts changed in a curve or irregularly due to the complications from the Maillard and lipid oxidization reactions. By comparing time‐courses of the levels of cysteine and Cys‐Amadori compounds, and 294 and 420 nm UV absorbance values in the reaction systems under 120°C with or without 2% methyl linoleate, it was revealed that the underlying lipid effect mechanism was to initially inhibit and later attend the Maillard reaction, leading to less formation of the Maillard compounds and generation of the lipid‐Maillard compounds. Abstract : Regulation rules in formation of Maillard and lipid‐Maillard flavors and the underlying affected Maillard mechanism were investigated when varying methyl linoleate level, reaction temperature and reaction time.